Characterisation of genes related to sesquiterpene compounds in agarwood production from Aquilaria malaccensis - Rofiza, Mansor (2019)
Aromatic essential oil extracted from A. malaccensis possess diverse applications in medicinal and perfume industry. High quality of agarwood is claimed due to present of high quantity and quality of sesquiterpenes as a market compounds. Despite the complicated process and long period in producing high quality agarwood in nature, it can be identified by elucidation of pathway via transcriptomic approaches. Targeted genes of sesquiterpene in A.malaccensis were identified through transcriptome data. cDNA library of three different sample (AM Infected-White, AM Infected-Black and AM Uninfected) were analyzed. The data was sequence with Illumina Next Generation Sequence (NGS) platform for the purpose of gene discovery in terpenoid biosynthesis. Data from sequencing was analysed with Blast2Go, Gene Ontology and KEGG software. The chemical compounds present in AM samples were determined by trapped volatile compounds in SPME and analysed with GC-FID. Gene Ontology (GO) for each sample had been employed to classify and arrange the particular functions. A total of 370,707 unigenes were divided into three categories with 26.77% in cellular components, 24.55% in molecular functions and 48.68% in biological process. To better assessment GO category, every GO term was further grouped to its parent category. The infected stem sample shown the highest number of gene regulated in all parent category. The transcripts were analyzed and deposited into BLASTX, six transcripts sequences were determined. That sequences were two genes of (-)-germacrene d synthase, two genes of δ-guaiene synthase, Sesquiterpene synthase and germacrene C synthase. The regulation levels of the 6 genes related to sesquiterpene were analyzed by observing the log fold change value. The positive value of the log fold change shows the upregulated and negative value shows the downregulated of the gene. Six transcripts of sesquiterpene group that were δ-guaiene synthase; AmguaS1, AmguaS2, and AmguaS3, (-)-Germacrene synthase AmGdS1, AmGdS2 and Sesquiterpene synthase were indicated present in infected and uninfected samples. Genes AmguaS1, AmguaS2, and AmguaS3 shown high regulated in the infected stem of A.malaccensis. Chemical profile analyzed by GC-FID, infected sample that shows an abundance of sesquiterpene compounds compare to uninfected sample. The sesquiterpene marker compounds that detected with high concentration in inoculated agarwood tree were agarospirol and Jinkol-eremol. The most upregulated genes that is δ-guaiene synthase were identified involve in biosynthesis process for production of marker compounds of agarwood and assumed to be involved in plant defense mechanism by agarwood formation synthesis.